1984
DOI: 10.1111/j.1600-079x.1984.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure of the Nerve Fibers and Pinealocytes in the Rat Pineal Stalk

Abstract: In view of the increasing interest in the central innervation of the mammalian pineal gland, this aspect was studied in depth in the rat. This species is especially suited since the nerve fibers in question form a distinct bundle running from the deep to the superficial pineal gland through the pineal stalk. The axons were counted and analysed ultrastructurally in the pineal stalks cut transversely at three levels (proximal, intermediate, and distal) relative to the neural axis and in longitudinal sections. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…A direct connection between the habenular nuclei and pineal gland has been suggested by short latencies in electrophysiological studies (Rønnekleiv et al 1980;Semm et al 1981;Reuss et al 1984), by HRP tracing (Dafny 1983;Møller andKorf 1983, 1987), and by electron-microscopic studies in the guinea pig . These connections, which may be interpreted as being part of a functional central innervation of the pineal gland, seem to involve the pineal stalk, which contains myelinated and unmyelinated fibres that decrease in number from proximal to distal (Luo et al 1984). However, combined neuronal tracing and immunocytochemistry of the habenular-pineal connection have not been conducted as yet.…”
Section: Extrasympathetic Innervation Of the Pineal Glandmentioning
confidence: 90%
“…A direct connection between the habenular nuclei and pineal gland has been suggested by short latencies in electrophysiological studies (Rønnekleiv et al 1980;Semm et al 1981;Reuss et al 1984), by HRP tracing (Dafny 1983;Møller andKorf 1983, 1987), and by electron-microscopic studies in the guinea pig . These connections, which may be interpreted as being part of a functional central innervation of the pineal gland, seem to involve the pineal stalk, which contains myelinated and unmyelinated fibres that decrease in number from proximal to distal (Luo et al 1984). However, combined neuronal tracing and immunocytochemistry of the habenular-pineal connection have not been conducted as yet.…”
Section: Extrasympathetic Innervation Of the Pineal Glandmentioning
confidence: 90%
“…Thus, at the ultrastructural level many myelinated nerve fibers are observed in the deep pineal gland and these fibers continue into the rostral part of the pineal stalk. However, in the stalk the number of myelinated fibers decreases and only a few are present in its rostral part (Møller and Korf 1983a;Luo et al 1984). Immunohistochemistry has indicated that central nerve fibers from the paraventricular nucleus contain vasopressin and oxytocin (Buijs and Pévet 1980;Nürnberger and Korf 1981).…”
Section: The Central Innervation Of the Mammalian Pineal Glandmentioning
confidence: 97%
“…The principal cell is the pineal parenchymal cell or pineocyte, which is surrounded by a stroma of fibrillary astrocytes admixed with sympathetic neurons [16-18]. The presence of glial cells in the pineal gland was first demonstrated by impregnation techniques with gold chloride-sublimate [15,19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to Burger et al [5], definite proof of the incospicious existence of pineal astrocytes comes from the occurrence of gliotic tissue in lesions such as craniopharyngiomas and hemangioblastomas. In addition to fibrillar astrocytes, there are some oligodendrocytes which are restricted to the proximal part of the stalk, near the deep pineal tissue where myelinated axons are abundant [18,20]. Adjacent to the gland there are ependymal cells and cells forming the choroid plexus of the third ventricle, as well as glial cells from the brainstem [21].…”
Section: Discussionmentioning
confidence: 99%